ASSESSMENT OF THE LEVEL OF FORMATION OF MORAL QUALITIES IN PRIMARY SCHOOL STUDENTS - Aziza Maxamatjonovna Mamatova (Bright Mind Publishing, 2025)
The article discusses the fundamentals of assessing the level of formation of moral qualities in primary school students.
Keywords: Primary school, student and morality, virtue and formation, indicator and level, assessment and approach.